Apocalypse illuminated: the visual exegesis of Revelation in medieval illustrated manuscripts - Emmerson, Richard Kenneth (The Pennsylvania State University Press, 2018)
"Studies the illustration of Revelation in manuscripts from the ninth to the fifteenth century. Examines how twenty-five of the most important illustrated Apocalypses illustrate the biblical text and interpret it for diverse audiences"--Provided by publisher